Prevalence, sub-types, and associated factors of anemia among inpatients at a tertiary psychiatric hospital in Tanzania: a cross-sectional study - Valeria Msigwa; Zahra Morawej; Ally Kinyaga; Shubi Ambwene Matovelo; Azan Nyundo (BMC Psychiatry)
Abstract Background Anemia has been linked to psychiatric disorders including depression, bipolar disorder, and schizophrenia. Studies have demonstrated an association between anemia and worsening clinical presentation and treatment outcomes of these disorders. This study aimed to assess the prevalence and factors associated with anemia among adult patients admitted at Mirembe National Mental Health Hospital (MNMH) in Dodoma, Tanzania. Methods A cross-sectional analytical study was conducted at MNMH among 265 adults admitted at the hospital. Socio-demographic and clinical variables were collected using a closed-ended questionnaire, and anemia and other hematological indices were assessed via complete blood count (CBC). Data were entered into an Open Data Kit (ODK) app and analyzed using SAS version 9.4. Chi-squared test was used initially to assess association between individual exposures and the outcome, anemia. Variables with a p-value < 0.20 from the chi squared analysis were fitted into a logistic regression model to determine their odds of association with anemia. Odds ratios from adjusted regression analysis were used to identify factors independently associated with anemia. Significance level was set at p value < 0.05. Results The prevalence of anemia among adult patients admitted at MNMH was 44% (CI 38.08, 50.36). The majority of participants had mild anemia (74.36%). Microcytic hypochromic and normocytic normochromic were the common types of anemia (47% and 46% respectively). Being male, institutionalization, and using Olanzapine was associated with anemia among participants at bivariate analysis, however, only institutionalization remained as a statistically significant factor associated with anemia at multivariable analysis (AOR:5.742, 95% CI 2.048, 16.105). Conclusions Comprehensive care strategies addressing anemia among psychiatric inpatients are crucial, extending beyond psychiatric symptoms to address factors related to prolonged admission, such as nutritional considerations. It is recommended that regular screening for anemia be implemented among psychiatric inpatients and efforts should be made to investigate and address the underlying causes of anemia among this population.